2022
DOI: 10.5489/cuaj.7859
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of two combinations of antibiotic used for perioperative prophylactic therapy during radical cystectomy: A retrospective cohort study

Abstract: Introduction: This retrospective cohort study aimed to compare primary and secondary outcomes of patients undergoing radical cystectomy according to two different perioperative antimicrobial therapy protocols in 2016. Methods: In this single-center, retrospective cohort study, we investigated data of 104 patients undergoing radical cystectomy due to bladder cancer from January 1, 2016, to December 31, 2016. According to perioperative antimicrobial prophylaxis, patients were divided into two groups: 48 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
1
Order By: Relevance
“…A retrospective cohort study of Andrijašević et al analysed the effect of the perioperative (24 h preoperatively and 48 h postoperatively) antimicrobial prophylaxis in patients with bladder cancer after radical cystectomy. This study has shown no statistical difference regarding the postoperative UTI rates between piperacillin/tazobactam 3 × 4.5 g and metronidazole 3 × 500 mg intravenously compared with ceftriaxone 1 × 2 g and metronidazole 3 × 500 mg intravenously [36].…”
Section: Managementcontrasting
confidence: 56%
“…A retrospective cohort study of Andrijašević et al analysed the effect of the perioperative (24 h preoperatively and 48 h postoperatively) antimicrobial prophylaxis in patients with bladder cancer after radical cystectomy. This study has shown no statistical difference regarding the postoperative UTI rates between piperacillin/tazobactam 3 × 4.5 g and metronidazole 3 × 500 mg intravenously compared with ceftriaxone 1 × 2 g and metronidazole 3 × 500 mg intravenously [36].…”
Section: Managementcontrasting
confidence: 56%